South African Responses to New Soviet Air Defence Systems in Angola in the 1980s - Szabo, Janet (Scientia Militaria - South African Journal of Military Studies, 2024)
Because of its air superiority during the counter-insurgency conflict against the South West Africa People’s Organisation, the South African Air Force had neglected to build up modern air and counter-air defences. When Soviet air defence systems were therefore deployed in Angola in the 1980s, they were forced to reconsider their tactics and responses to the war. The Soviet systems included early warning networks, surface-to-air missiles and anti-aircraft guns to cover troops advancing in the field, and fighter aircraft. While this build-up was also observed in the neighbouring Southern African countries and had the appearance of a purely defensive stance, given Soviet air defence doctrine, South Africa viewed this as the first steps to offensive actions in Angola and possibly Namibia (then South West Africa) and the start of a dangerous escalation in the military situation. In response, the SADF adopted a strong defensive stance and improved its own air defence capabilities to ensure that it was not outclassed. The South African Air Force also introduced new tactics. These included the introduction of toss-bombing, making greater use of precision-guided missiles and bombs, and investing more in research in terms of missiles and new technology for their aircraft.